Technical characteristics and features of the most widely-known optoelectronic systems in the field of human moving biomechanics - K. Gianikellis (Asociación Española de Ciencias del Deporte, 2010)
Comparisons between the merits of many different motion analysis systems is a very difficult task because their published specifications are obtained in a widely varying conditions and in some cases refer only to the performance of small components of an integrated system. The main purpose of this study is the introduction of the reader to the most important tecnologic characteristics that define the performance of the modern optoelectronic systems on the basis of data acquisition and signal processing. The evolution of these systems during the last two decades brought about a need for determination of objective criteria and standarized procedures that allow potential users evaluate different systems before spend money. In short, the decision for an optoelectronic system should be made on the basis of the investigations´ particular purposes, systems' performance and price. KEY WORDS: Photoinstrumentation, optoelectronic systems, cinematic analysis, Biomechanics